PERBAIKAN SISTEM OPERASIONAL USAHA TRAVEL SEBAGAI UPAYA PENINGKATAN KUALITAS MANAJEMEN - Azhari, Azhari; Moh. Mustofa; Muslinawati, Retno; Dwi Meisari, Erika; Setia Anggarista, Erika Tri (Jurnal Abdi Masyarakat, 2024)
Activity Aims To Improve The Travel Business Operational System As An Effort To Improve Management Quality Based on the results of assistance for the "Nafis Transport" travel business, it can be concluded that this assistance is specifically focused on improving service SOPs for customers and fleet management. The impact of this assistance shows that there are benefits for "Nafis Transport" management in understanding the systematics and flow of service to customers as well as better travel management. This increased understanding allows companies to provide services to customers more efficiently and manage their transportation fleet in a more structured manner. The evaluation results also reflect the lack of human resources for good administrative preparation. The evaluation suggests that addressing these challenging needs is done through a more advanced approach, perhaps by providing additional training or strengthening the administration team with appropriate resources. Along with improving SOPs, addressing limited human resources is very important to ensure long-term improvements and improvements in operational quality for attenuation objects.